On the infrared divergence and global colour in N $$ \mathcal{N} $$ = 4 Yang-Mills theory - Su Yu Ding; Joanna Karczmarek; Gordon W. Semenoff (Journal of High Energy Physics, 2020)
Abstract The N $$ \mathcal{N} $$ = 4 superconformal Yang-Mills theory on flat four-dimensional Minkowski space is a de-confined gauge theory in the sense that the string tension for fundamental representation coloured quarks vanishes. In fact, static fundamental representation quarks which lie in certain half-BPS super-multiplets do not interact at all. An interesting question asks whether such quarks would carry a well-defined global colour charge which, when the gauge is fixed, should have the status of an internal symmetry. We shall present a simple paradigmatic model which suggests that the answer to this question lies in the way in which infrared divergences are dealt with.